Possíveis alterações na qualidade do ar durante a pandemia de Covid-19 - Godinho, Letícia Silva (Universidade Federal de São Carlos, 2022)
Air is a natural resource that is indispensable for life on Earth. However, for years the atmospheric quality has been affected by intense processes of urbanization, industrialization, and demographic growth. The main sources of pollutants emissions into atmosphere come from anthropogenic actions, such as industrial activities, incomplete combustion processes, and excessive use of motor vehicles. Acute episodes of air pollution throughout history have triggered concern and need for mitigating actions. In light of this, research was initiated to understand the air constitution, as well as control measures through periodic monitoring of pollutants concentrations and setting of air quality standards, determined according to nature of emission and risks posed to human and environmental health. Currently, occurrence of pandemic crisis resulting from new coronavirus, a highly contagious disease, has required the adoption of emergency preventive measures to reduce as much as possible the rapid pace of dissemination, ensuring population survival. One adopted measure was social isolation, which restricted circulation of population, automobiles, and operation of industries. With this, it was possible to observe an apparent reduction of pollutants in atmosphere. This study was developed with objective of analyzing impact of social isolation on air quality in Metropolitan Region of São Paulo, through analysis of articles, selected by exploratory research, and air quality monitoring databases, contributing to proof of relationship between anthropic actions and environment. Thus, it was possible to evaluate the changes in air quality parameters before, during, and after social isolation, concluding that during period of reduction of pollutant sources, the air quality significantly improved.
Possible changes in air quality during the Covid-19 pandemic
Keywords: Qualidade do ar; Poluição do ar; Isolamento social; Air quality; Air pollution; Social isolation; Pandemia de Covid-19; Pandemic Covid-19; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::CONTROLE DA POLUICAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO